Detection of ictal apnea refines the clinical spectrum of ATRX syndrome - Galal Banat; Friedrich G. Woermann; Rami Abou Jamra; Christian G. Bien; Christian Brandt (Epilepsy & Behavior Reports)
Alpha-thalassemia X-linked intellectual disability syndrome (ATRX) is a rare genetic disorder caused by mutations in the ATRX gene. It is characterized by distinct dysmorphic features, alpha thalassemia, varying degrees of intellectual disability, and the presence of epilepsy in approximately 30 % of affected individuals. We present the case of a 36-year-old patient with severe intellectual disability and epilepsy due to a hemizygous pathogenic variant, c.736c > T, p. (Arg246Cys), in the ATRX gene. During inpatient treatment, numerous respiratory pauses were detected. Repeated video EEG recordings revealed seizure patterns with a left frontocentral origin and an occasional spread to the bifrontal region and episodes of apnea without an EEG correlate. This case report adds to the current literature, as it shows a co-occurrence of ictal and non-ictal apnea in ATRX syndrome, expanding our understanding of respiratory disturbances in this rare genetic disorder.